PENGARUH UKURAN PERUSAHAAN, TINGKAT UTANG DAN BIAYA OPERASIONAL TERHADAP BEBAN PAJAK PENGHASILAN BADAN - Febriana, Nurfadilla; Yusuf, Nur’aini (Jurnal Nusa Akuntansi, 2025)
This research aims to analyze and provide empirical evidence of the influence of company size, debt levels and operational costs on corporate income tax burden. This type of research is associative quantitative using secondary data in the form of annual financial reports of food and beverage sub-sector companies registered in Indonesia Stock Exchange (IDX). during the period 2019 to 2023. The sample selection procedure in this study used a purposive sampling method and obtained results from 18 companies that met the criteria. The variables used in this research are company size as the first independent variable, debt level as the second independent variable and operational costs as the third independent variable and corporate income tax burden as the dependent variable. The analysis technique used is panel data regression analysis using E- views 12 software. The results of this study state that company size and debt levels have a significant effect on the corporate income tax burden, operational costs have no effect on the corporate income tax burden.